Spanish Prints from the Peninsular War: Propaganda, Commemoration and Testimony Estampas españolas de la Guerra de la Independencia: propaganda, conmemoración y testimonio - José Manuel MATILLA (Cuadernos Dieciochistas)
Prints were a remarkable propaganda instrument during the Peninsular War. Since the mid 18th century the State had been encouraging the development of engraving and this favoured the existence of printmakers who satisfied the requirements of the market during these years. This market can be tracked thanks to the advertisements published in the periodical press. Production revolved around satire, portraits and narrative representations. As opposed to these mainly propagandistic prints, Francisco de Goya’s Disasters of War constitute a counterpoint in which the author offers a critical and personal point of view. Las estampas constituyeron un notable instrumento de propaganda durante la Guerra de la Independencia. La labor que el Estado había desarrollado desde mediados del siglo XVIII para el fomento del grabado favoreció la existencia de grabadores que satisficieron la demanda del mercado en estos años. Un mercado que es posible seguir gracias a los anuncios insertados en la prensa periódica. Sátiras, retratos y representaciones narrativas constituyen los tres ejes alrededor de los que gira esta producción. Frente a estas estampas de función eminentemente propagandística, los Desastres de la guerra de Francisco de Goya constituyen un contrapunto en el que el autor ofrece una visión crítica y personal.